Men Who Specifically Seek Unprotected Sex Partners via the Internet Whose Profiles Are the Most Searched for by Other Site Users? - Klein, Hugh (Journal of gay & lesbian social services, 2010)
Men who have sex with men (MSM) account for the largest number of persons diagnosed with AIDS in the United States, with higher than-average rates of drug use and unprotected sex being cited as the principal reasons underlying their high rates of HIV infection. Recent evidence has suggested that the use of Web sites specifically designed to promote unsafe sexual practices may be particularly common among MSM, therebyfostering their risky behaviots. In light of these findings, the present study which compares HIV risk behaviors sought by men whose profiles are among the most frequently brought up in searches to those whose profiles ate not aspopular with other site users, is based on a content analysis of 1,316 ads/profiles posted on one of the most popular MSM Web sites that specifically fosters unprotected sex. Ads/profiles were selected randomly based on the American ZIP code of residence. Data were collected between September 2006 and January 2007. Rates of advertised-for high-risk sexual behaviots were very high both for men whose profiles were among the most popular and those whose profiles were not, particularly for oral sex involving ejaculation into the mouth, anal sex involving ejaculation into the anus, multiple partner sex, and fetching. Analytical comparisons of these groups showed that the most searched for profiles weæ thosepromoting the highest levels ofrisky behaviors and the greatest propensity toward wanting to engage in high-risk activities. Ihe HIV intenention-related implications of these findings are discussed